Comparative Effectiveness of Pylorus-Preserving Versus Standard Pancreaticoduodenectomy in Clinical Practice. Issue 4 (April 2020) - Calderon, Esteban; Day, Ryan W.; Stucky, Chee-Chee; Gray, Richard J.; Pockaj, Barbara A.; Chang, Yu-Hui; Wasif, Nabil
Abstract : Objectives: We compared risk-adjusted short- and long-term outcomes between standard pancreaticoduodenectomy (SPD) and a pylorus-preserving pancreaticoduodenectomy (PPPD). Methods: The National Cancer Database was queried for the years 2004 to 2014 to identify patients with adenocarcinoma of the pancreatic head undergoing SPD and PPD. Margin status, lymph node yield, length of stay (LOS), 30- and 90-day mortality, and overall survival were compared. Results: A total of 11, 172 patients were identified, of whom 9332 (83.5%) underwent SPD and 1840 (16.5%) PPPD. There was no difference in patient age, sex, stage, tumor grade, radiation treatment, and chemotherapy treatment between the 2 groups. Total number of regional lymph nodes was examined, and surgical margin status and overall survival were also comparable. However, patients undergoing PPPD had a shorter LOS (11.3 vs 12.3 days, P < 0.001), lower 30-day mortality (2.5% vs 3.7%, P = 0.02), and 90-day mortality (5.5% vs 6.9%, P = 0.03). On multivariate analyses, patients undergoing SPD were at higher risk for 30-day mortality compared with PPPD (odds ratio, 1.51; 95% confidence interval, 1.07–2.13). Conclusions: Standard pancreaticoduodenectomy and PPPD are oncologically equivalent, yet PPPD is associated with a reduction in postoperative mortality and shorter LOS. Abstract : Supplemental digital content is available in the text.